PREVENTION AND REHABILITATION OF ANKLE SPRAIN IN SOCCER TRAINING - Sun,Ruxun (2023)
ABSTRACT Introduction In soccer training, many impacts in running and defense make ankle sprain a very common sports injury; therefore, prevention and rehabilitation management of ankle sprain is particularly important. Objective Explore the strategy of preventing and rehabilitating ankle sprain in soccer training. Methods 10 athletes with ankle sprain were selected and randomly divided into the experimental and control group. Both groups received rehabilitation training, the control group received only manual therapy, and the experimental group received active and passive rehabilitation management. The indices relevant to ankle rehabilitation were analyzed daily: active extension and flexion angle, in addition to the degree of joint edema. Results By the third day, the experimental group’s recovery rate was significantly higher. By the end of the seventh day, the active plantar flexion angle in the control group was 28.0133, while in the experimental group, it was 32.0512. As for the degree of joint swelling on day 5, the experimental group was 2.2059 and 1.0057 in the control group. The control group only achieved this level of recovery in the experimental group on the seventh day. Conclusion Using comparative analysis, the rehabilitation strategy associated with the active and passive techniques proposed in this article showed a better performance than the traditional protocol. Studies are suggested popularizing rehabilitation combined with active training with passive traction. Level of evidence II; Therapeutic studies - investigation of treatment results.